2018
DOI: 10.1152/ajpendo.00130.2018
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of short-term treatment with the phosphodiesterase type 5 inhibitor tadalafil on long bone development in young rats

Abstract: Cyclic GMP (cGMP) is an important intracellular regulator of endochondral bone growth and skeletal remodeling. Tadalafil, an inhibitor of the phosphodiesterase (PDE) type 5 (PDE5) that specifically hydrolyzes cGMP, is increasingly used to treat children with pulmonary arterial hypertension (PAH), but the effect of tadalafil on bone growth and strength has not been previously investigated. In this study, we first analyzed the expression of transcripts encoding PDEs in primary cultures of chondrocytes from newbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…Similar observations were found by Pal et al in a model of mouse calvarial osteoblasts treated with sildenafil and vardenafil, which increased surface referent bone formation and serum bone formation marker P1NP and the expression of vascular endothelial growth factor and its receptor 2 in bones and osteoblasts, alongside increased skeletal vascularity [27]. However, neutral results came from an interesting study by Wang et al conducted on the primary cultures of chondrocytes from newborn rat epiphyses [28]. The authors demonstrated that this cell line highly expressed PDE5 and that a short-term tadalafil treatment in growing rats at doses comparable to those used in children with pulmonary arterial hypertension has neither obvious beneficial effects on long bone growth nor any observable adverse effects on growth plate structure and trabecular and cortical bone structure [28].…”
Section: Tadalafil and Bone: Preclinical Observationssupporting
confidence: 76%
See 1 more Smart Citation
“…Similar observations were found by Pal et al in a model of mouse calvarial osteoblasts treated with sildenafil and vardenafil, which increased surface referent bone formation and serum bone formation marker P1NP and the expression of vascular endothelial growth factor and its receptor 2 in bones and osteoblasts, alongside increased skeletal vascularity [27]. However, neutral results came from an interesting study by Wang et al conducted on the primary cultures of chondrocytes from newborn rat epiphyses [28]. The authors demonstrated that this cell line highly expressed PDE5 and that a short-term tadalafil treatment in growing rats at doses comparable to those used in children with pulmonary arterial hypertension has neither obvious beneficial effects on long bone growth nor any observable adverse effects on growth plate structure and trabecular and cortical bone structure [28].…”
Section: Tadalafil and Bone: Preclinical Observationssupporting
confidence: 76%
“…However, neutral results came from an interesting study by Wang et al conducted on the primary cultures of chondrocytes from newborn rat epiphyses [28]. The authors demonstrated that this cell line highly expressed PDE5 and that a short-term tadalafil treatment in growing rats at doses comparable to those used in children with pulmonary arterial hypertension has neither obvious beneficial effects on long bone growth nor any observable adverse effects on growth plate structure and trabecular and cortical bone structure [28]. Finally, we demonstrated that human osteoblasts (SAOS-2) express significant levels of both PDE5 mRNA and protein and that their exposure to increasing concentrations of tadalafil [10(-8)-10(-7) M] decreased PDE5 mRNA and protein expression.…”
Section: Tadalafil and Bone: Preclinical Observationsmentioning
confidence: 99%
“…In addition to the treatment of erectile dysfunction, PDE-5-Is are widely used in clinical practice for the treatment of both primary and secondary pulmonary hypertension. An important feature in the correction of PDE-5-IS is not only vasodilation, but also the prevention of remodelling vessels (Wang et al 2018). The controlled randomized trial revealed the presence of a vasorelaxating effect in conditions of pulmonary arterial hypertension in sildenafil, vardenafil, and tadalafil (Mokry et al 2017) Due to the accumulation of cGMP, PDE-5 inhibitors may have a stimulating influence on the metabolic pathway of the formation of the nitrogen oxide NO/cGMP/ PDE.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, PDE5A is expressed in the brain, and its inhibition affects neurogenesis, memory, and stroke progression (26)(27)(28). PDE5A is also expressed in chondrocytes, but inhibiting PDE5A in 1-mo-old rats for 3 wk did not affect long bone growth or bone modeling (29). Other studies on putative skeletal effects of PDE5A inhibition in animal models have yielded inconsistent results, including hyperresorption and low bone density (30), positive effects on bone in ovariectomized and glucocorticoid-treated mice (31,32), and accelerated fracture healing (33).…”
Section: Significancementioning
confidence: 99%